Revisiting aspect and Aktionsart : a corpus approach to Koine Greek event typology - Pang, Francis G. H. (Linguistic Biblical Studies, 2016)
In Revisiting Aspect and Aktionsart, Francis G.H. Pang employs a corpus approach to analyze the relationship between Greek aspect and Aktionsart . Recent works have tried to predict the meanings that emerge when a certain set of clausal factors and lexical features combine with one of the grammatical aspects. Most of these works rely heavily on Zeno Vendler's telicity distinction. Based on empirical evidence, Pang argues that telicity and perfectivity are not related in a systematic manner in Koine Greek. As a corollary, Aktionsart should be considered an interpretive category, meaning that its different values emerge, not from the interaction of only one or two linguistic parameters, but from the process of interpreting language in context.